TRP channels: a provocative rationalization for local Ca2+ control in arterial tone development - El-Lakany, Mohammed A.; Welsh, Donald G. (Frontiers in Physiology, 2024)
Arterial networks are controlled by the consolidated output of stimuli that set "how much" (magnitude) and "where" (distribution) blood flow is delivered. While notable changes in magnitude are tied to network wide responses, altered distribution often arises from focal changes in tone, whose mechanistic foundation remains unclear. We propose herein a framework of focal vasomotor contractility being controlled by pharmacomechanical coupling and the generation of Ca 2+ waves via the sarcoplasmic reticulum. We argue the latter is sustained by receptor operated, transient receptor potential (TRP) channels through direct extracellular Ca 2+ influx or indirect Na + influx, reversing the Na + /Ca 2+ exchanger. We view this focal regulatory mechanism as complementary, but not redundant with, electromechanical coupling in the precision tuning of blood flow delivery.